2014
DOI: 10.1097/icu.0000000000000049
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the design of artificial corneas

Abstract: Purpose of review: Artificial corneas are being developed to meet a shortage of donor corneas as well as to address cases where allografting is contraindicated. A range of artificial corneas has been developed. Here we review several newer designs and especially those inspired by naturally occurring biomaterials found with the human body and elsewhere. Summary:More recent attempts at making artificial corneas have taken a more nature-based or nature-inspired approach. Several will in the near future be likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…The supply of donor corneas for transplantation does not meet the demand in many countries. This prompted researchers to look for alternatives including corneal constructs or equivalents (Griffith and Harkin, 2014). In recent years, there was substantial progress in making corneal stromal constructs based on compressed collagen with or without stromal keratocytes or fibroblasts.…”
Section: Corneal Stromal Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…The supply of donor corneas for transplantation does not meet the demand in many countries. This prompted researchers to look for alternatives including corneal constructs or equivalents (Griffith and Harkin, 2014). In recent years, there was substantial progress in making corneal stromal constructs based on compressed collagen with or without stromal keratocytes or fibroblasts.…”
Section: Corneal Stromal Wound Healingmentioning
confidence: 99%
“…In recent years, there was substantial progress in making corneal stromal constructs based on compressed collagen with or without stromal keratocytes or fibroblasts. Decellularized corneal stroma has also been used, as well as silk-fibroin or synthetic materials (Griffith and Harkin, 2014). Such constructs can be transplanted into a trephined bed in the stroma to replace damaged tissue, and some have entered clinical trials (Griffith and Harkin, 2014).…”
Section: Corneal Stromal Wound Healingmentioning
confidence: 99%
“…However, there is a severe worldwide donor shortage, and not all conditions are amenable to donor grafting. 15 Here, hydrogel implants were molded into implants the shape and size of human corneas (500μm thick, 12 mm diam). In compliance with the OECD Principle of Good Laboratory Practice (GLP), ENV/MC/CHEM (98) 17,1997, and with local ethical permission from Stockholms Norra Djurförsöksetiska Nämnd, implants was grafted into the corneas of four Gottingen mini-pigs by anterior lamellar keratoplasty, after excision of the pigs own corneal tissues.…”
Section: Propertiesmentioning
confidence: 99%
“…To date, numerous studies have reported various artificial cornea, including keratoprostheses and tissue-engineered (TE) constructs as alternatives to donor corneas45678. Nevertheless, most of these artificial corneas only partially satisfy the requirements, including biocompatibility, transparency, flexibility, and sufficient suturability strength.…”
mentioning
confidence: 99%